Why does air passage over forest yield more rain?: examining the coupling between rainfall, pressure and atmospheric moisture content - Makarieva, A.M.; Gorshkov, V.G; Sheil, D.; Nobre, A.D; Bunyard, P; Li, B.L. (American Meteorological Society, 2014)
The influence of forest loss on rainfall remains poorly understood. Addressing this challenge, Spracklen et al. recently presented a pantropical study of rainfall and land cover that showed that satellite-derived rainfall measures were positively correlated with the degree to which model-derived air trajectories had been exposed to forest cover. This result confirms the influence of vegetation on regional rainfall patterns suggested in previous studies. However, the conclusion of Spracklen et al.—that differences in rainfall reflect air moisture content resulting from evapotranspiration while the circulation pattern remains unchanged—appears undermined by methodological inconsistencies. Here methodological problems are identified with the underlying analyses and the quantitative estimates for rainfall change predicted if forest cover is lost in the Amazon. Alternative explanations are presented that include the distinct role of forest evapotranspiration in creating low-pressure systems that draw moisture from the oceans to the continental hinterland. A wholly new analysis of meteorological data from three regions in Brazil, including the central Amazon forest, reveals a tendency for rainy days during the wet season with column water vapor (CWV) exceeding 50 mm to have higher pressure than rainless days, while at lower CWV, rainy days tend to have lower pressure than rainless days. The coupling between atmospheric moisture content and circulation dynamics underlines that the danger posed by forest loss is greater than suggested by consideration of moisture recycling alone.